Adherencia al tratamiento antihipertensivo y calidad de vida en instituciones de segundo nivel de atención - Sara Sahury; Andrea Poleth Castellanos Ulloa; Deysi Julissa Díaz Valle; Sinthia Bonilla; Ramón Maradiaga; Edna J. Maradiaga (Revista Médica Hondureña)
Introduction: Adherence to treatment is a public health problem, with importance in chronic disease therapies. Poor adherence to long-term treatment compromises treatment effectiveness and directly influences quality of life. Objective:To establish the relationship between adherence to treatment and quality of life in adult hypertensive patients in two second level hospitals. Methods: Cross-sectional descriptive study, with analysis of association, non-probabilistic convenience sampling, sample was selected using the Open Epi online programme, resulting in 206 patients who met the inclusion criteria. Adherence was measured with the Morisky-Green-Levine test and quality of life with MINICHAL. Data were analyzed in SPSS Statistic 21.0; univariate analysis, calculating frequencies, percentages and bivariate analysis (association between adherence/adherence factors and quality of life), chi-square test and binary logistic regression model were applied. Ethical approval was obtained. Results: The study population was predominantly female, aged 51-60 years, literate, married, poor. 71.4% (147) were adherent to treatment. The quality of life was medium-high in 80.1% (165). There was an association between adherence and schooling (p<0.01), poverty level (p<0.01), use of other drugs (p<0.01). No association was found between adherence and quality of life (p<0.1) Discussion: Adherence to treatment was high. Adherent patients had a medium-high quality of life, non-adherent patients a low quality of life; patients with polypharmacy, higher education and socioeconomic status had better adherence to treatment.